2021
DOI: 10.1007/s11760-021-01988-1
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning framework using CNN and stacked Bi-GRU for COVID-19 predictions in India

Abstract: The novel coronavirus infection (COVID-19) first appeared in Wuhan, China, in December 2019. COVID-19 declared as a global pandemic by the WHO was the most rapidly spreading disease all across the world. India, the second most populated nation in the world, is still fighting it, when coronavirus reached the stage where community transmission takes place at an exponential rate. Therefore, it is crucial to examine the future trends of COVID-19 in India and anticipate how it will affect economic and social growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Bi-GRU is a composite of two GRUs that operate in opposing directions, with one moving forward and the other moving backward. Similarly to Bi-LSTM, the outputs of these two GRUs are merged to obtain the final result [49]. Using Bi-RNN, the model is capable of understanding the intricate connections between these parameters, which allows for more precise and reliable predictions [50].…”
Section: Bidirectional Rnn (Bi-lstm and Bi-gru)mentioning
confidence: 99%
“…Bi-GRU is a composite of two GRUs that operate in opposing directions, with one moving forward and the other moving backward. Similarly to Bi-LSTM, the outputs of these two GRUs are merged to obtain the final result [49]. Using Bi-RNN, the model is capable of understanding the intricate connections between these parameters, which allows for more precise and reliable predictions [50].…”
Section: Bidirectional Rnn (Bi-lstm and Bi-gru)mentioning
confidence: 99%
“…For example, Chen, Qi, et al (2021) applied Bi-GRU to predict wind power, and the results proved its superior prediction performance compared with LSTM and GRU. Ahuja et al (2022) used CNN and stacked Bi-GRU to predict the COVID-19 cases. The experimental result showed that the proposed model was highly reliable over the gaussian process regression model (Schulz et al, 2018).…”
Section: Recurrent Neural Network Variantsmentioning
confidence: 99%
“…Recently, deep learning models have been applied to the prediction of time series problems, such as temperature prediction [ 22 ] and stock prediction [ 23 ], which have achieved good results. Given the strong correlation between COVID-19 and time, many researchers have used deep learning models such as RNN, LSTM, BILSTM, CNN, GRU, and some hybrid models [ 24 , 25 , 26 , 27 , 28 , 29 ] to predict COVID-19 cases. For example, Xu et al [ 29 ] used CNN, LSTM, and CNN-LSTM models to predict COVID-19 cases in Brazil, India, and Russia and found that the LSTM model performed the best among the three models.…”
Section: Introductionmentioning
confidence: 99%